2018
DOI: 10.31867/2523-4544/0011
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of application the biological preparations and growth stimulators in the pea crops in conditions of the Northern Steppe of Ukraine

Abstract: Дніпровський державний аграрно-економічний університет, вул. Сергія Єфремова, 25, м. Дніпро, 49027, Україна Встановлена висока ефективність застосування препарату реаком-С-боби в нормі 4 л/т для інкрустації та фосформобілізуючих бактерій в нормі 455 мл/т для інокуляції посівного матеріалу. При використанні вказаних препаратів має місце збільшення висоти рослин гороху, фотосинтетичного потенціалу листкового апарату до 16-18 % та елементів продуктивності (кількість бобів з рослини, кількість зерен в бобі, ма… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Завдяки високій чутливості кореневої системи зернобобових культур до ураження рослин ґрунтовими патогенами (збудниками кореневих гнилей) зменшується не тільки їх врожайність, а й відбувається значне порушення обміну речовин, і погіршується якість як зерна, так і зеленої маси [13].…”
Section: землеробство меліорація ґрунтознавство агрохімія 19unclassified
“…Завдяки високій чутливості кореневої системи зернобобових культур до ураження рослин ґрунтовими патогенами (збудниками кореневих гнилей) зменшується не тільки їх врожайність, а й відбувається значне порушення обміну речовин, і погіршується якість як зерна, так і зеленої маси [13].…”
Section: землеробство меліорація ґрунтознавство агрохімія 19unclassified
“…Dubey et al (2020) show the role of biostimulants in the mechanisms of protection of Fabaceae plants from abiotic stresses, stimulation of growth processes, nutrient recycling, improvement of grain quality, and increase of crop yields. A lot of evidence has been accumulated that demonstrates the positive results of using growth regulators in soybean (Shepilova et al, 2021), pea (Nebaba, 2023), bean (Pyda et al, 2021), and cereal grains (Lemishko et al, 2022), which contribute to a significant increase in the activity of symbiotic and associative nitrogen fixation and increase yields. N. Khan et al (2020) showed that chickpea plants treated with growth regulators (salicylic acid, putrescine) had a higher height and weight of the aerial parts of plants, increased chlorophyll, protein, and sugar content, and increased yield.…”
Section: Introductionmentioning
confidence: 99%